FAKTOR PENDORONG DAN PENGHAMBAT PEMBANGUNAN WISATA EDUKASI PERTANIAN DI BALAI BENIH HORTIKULTURA KABUPATEN GARUT - Syifa Al Mani; Lucyana Trimo (Universitas Galuh Ciamis, 2021)
Agro tourism is tourism sector development form which changes by the times. Cultivation activities coupled with agricultural land and activities can be used as the way to develop related sector. Horticultural seed center (BBH) as a regional technical unit under Department of Agriculture has a plan to optimize the institution’s role and function through the agricultural edutourism project by seeing the potential and uniqueness of tourist-destination of Garut Regency. The institution’s operational activities faced with budget problem, limited human resoureces in terms of number and competencies, also the existence of inadequate facilities and infrastucture. Those things can affect the productivity and hinder project realization. This study aims to identify supporting and obstacle factors that influence to agro-edutourism project in BBH. The research using a qualitative methods and case study techniques to expolate various data according to object’s condition. The data were obtained from observation, in-depth interviews, documentation, and literature studies, then analyzed by using IFAS and EFAS matrices and it can be taken into consideration for the project. The driving factors are : condition of supportive resources, the concept is oriented towards education, there are no competitors yet, commitment and support form stakeholders, and agricultural sector still dominates economic activity. The inhibiting factors are : inadequate planning with main task and function, limited resources, high dependency on government, leader’s changing affects on project completion, lack of socialization by BBH to the community, also the COVID-19 pandemic.